(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Review of clinical, subclinical and surgical results of total repair of tetralogy of Fallot in children under 1 year old at Hanoi Heart Hospital and Thanh Hoa Children’s Hospital. Methods: A cross-sectional descriptive study on 115 patients at Thanh Hoa Children’s Hospital and Hanoi Heart Hospital in 2016. Results: Pediatric patients have typical clinical symptoms such as slow weight gain (73%), syncope (7.8%), dyspnoea (20%), cyanosis (40%), and cyanosis of different levels (84, 5). 3%), systolic murmur (100%), SpO2 less than 80% (21.7%). The patient had an increase in erythrocyte index (14.8%) and hematocrit (0.9%). On the X-ray film, the lungs are bright (48.7%), and the heart is concentric (26.1%). The results of the electrocardiogram showed that the proportion of patients with right ventricular hypertrophy was 39.1%. The proportion of patients with right bundle branch block accounts for 13%. Echocardiographic results showed that the majority of patients had 1 ventricular septal defect (98.3%). Most of the pediatric patients had stoma in the peri-membrane position (98.3%). The mean right ventricular–pulmonary difference was 83.7±20.8 mmHg (40 – 153 mmHg). The proportion of patients with a gradient over 75 mmHg is 60%. The mean left ventricular function (EF) was 68.8±6.9% (54-85%); The mean right ventricular dilatation index was 0.6±0.1 (0.4–1.1) and the mean right ventricular funnel diameter was 4.2±1.3 mm (2-7mm). Conclusion: Children under 1 year of age with tetralogy of Fallot who were indicated for total repair surgery in the study had clinical and subclinical characteristics similar to those of older children, with characteristics of patients with tetralogy of Fallot.